2016
DOI: 10.1371/journal.pone.0160553
|View full text |Cite
|
Sign up to set email alerts
|

Serological Evidence of Lyssaviruses among Bats on Southwestern Indian Ocean Islands

Abstract: We provide serological evidence of lyssavirus circulation among bats on southwestern Indian Ocean (SWIO) islands. A total of 572 bats belonging to 22 species were collected on Anjouan, Mayotte, La Réunion, Mauritius, Mahé and Madagascar and screened by the Rapid Fluorescent Focus Inhibition Test for the presence of neutralising antibodies against the two main rabies related lyssaviruses circulating on the African continent: Duvenhage lyssavirus (DUVV) and Lagos bat lyssavirus (LBV), representing phylogroups I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…This study identified seven LBV-, 19 DUVV-, and 2 EBLV-1-positive sera samples collected from different bat species within the island. On the contrary, real-time RT-PCR could not amplify lyssavirus sequences from the bat samples and hence failed to document an active infection [41].…”
Section: Mauritiusmentioning
confidence: 94%
See 4 more Smart Citations
“…This study identified seven LBV-, 19 DUVV-, and 2 EBLV-1-positive sera samples collected from different bat species within the island. On the contrary, real-time RT-PCR could not amplify lyssavirus sequences from the bat samples and hence failed to document an active infection [41].…”
Section: Mauritiusmentioning
confidence: 94%
“…In this study, only two bat sera samples were positive for LBV seroprevalence while two other sera were positive for DUVV prevalence out of eight samples that were tested. None of the samples were positive for lyssavirus RNA by real-time RT-PCR [41]. Many other viruses (Ebola, coronavirus, rabies, etc.)…”
Section: Comoros Islandmentioning
confidence: 98%
See 3 more Smart Citations